Business leadership in South Africas 1994 reforms - Shapiro, Ian, (SAGE Knowledge. Cases., 2017)
The democratic, multi-racial election of 1994 ended the apartheid era in South Africa. Leading up to that historic change, a group of white business leaders saw that their country might follow one of two paths. It might experience an overthrow of minority rule, ending up something like Cuba, with a revolution and nationalization of major industries and isolation from much of the world. Alternatively, it could follow a path something more like Brazil, which ended military leadership and redemocratized to tolerate social change and political crises while encouraging a dramatic business growth.